2021
DOI: 10.1186/s42523-020-00070-4
|View full text |Cite
|
Sign up to set email alerts
|

The porcine respiratory microbiome: recent insights and future challenges

Abstract: Understanding the structure of the respiratory microbiome and its complex interactions with opportunistic pathogenic bacteria has become a topic of great scientific and economic interest in livestock production, given the severe consequences of respiratory disease on animal health and welfare. The present review focuses on the microbial structures of the porcine upper and lower airways, and the factors that influence microbiome development and onset of respiratory disease. Following a literature search on PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 70 publications
(128 reference statements)
5
38
0
Order By: Relevance
“…Lower bacterial richness and evenness was found in the nasal microbiota in the farms with disease, when they were compared with the animals from the healthy control farms. This finding is supported by many other studies that established that lower alpha diversity values are linked to poor health status in pigs, but also in other species [ 13 , 16 , 17 ]. Here, a lower microbial richness of the nasal cavity in the disease farms may be associated with the proliferation of the undesirable taxonomic groups that would lead to systemic infections.…”
Section: Discussionsupporting
confidence: 84%
“…Lower bacterial richness and evenness was found in the nasal microbiota in the farms with disease, when they were compared with the animals from the healthy control farms. This finding is supported by many other studies that established that lower alpha diversity values are linked to poor health status in pigs, but also in other species [ 13 , 16 , 17 ]. Here, a lower microbial richness of the nasal cavity in the disease farms may be associated with the proliferation of the undesirable taxonomic groups that would lead to systemic infections.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, antimicrobials have the potential to disrupt the beneficial microbial communities of the microbiota [7,13,14]. Therefore, alternative tools to control diseases while ensuring balanced costs and low economic loses are of great interest [15], including those directed to the development and maintenance of healthy microbial communities [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the microbiota begins to stabilize and progress toward and adult-like composition 2-3 weeks after the weaning (Slifierz et al, 2015;Cortes et al, 2018). As previously described in the gut (Mach et al, 2015), weaning is the critical period for the establishment of a robust and stable adult-like microbiota composition in piglets (Pirolo et al, 2021). Alongside weaning, other key environmental factors can modify the composition of the URT microbiota early in life, including the addition or removal of feed antibiotics (Zeineldin et al, 2018;Correa-Fiz et al, 2019;Mou et al, 2019;Zeineldin et al, 2019), gaseous ammonia concentration (Michiels et al, 2015;Wang et al, 2019), type of floor (Megahed et al, 2019) or feeding strategies (Weese et al, 2014).…”
Section: Environmental Stressors As Drivers Of the Respiratory Microbiota Composition And Dynamics Across Speciesmentioning
confidence: 76%
“…In cows and feedlot cattle, several studies have reported how a healthy respiratory microbiota is established in the airways and surveyed which host and environmental factors drive it (Timsit et al, 2016;Hall et al, 2017;Holman et al, 2017;Nicola et al, 2017;Zeineldin et al, 2017a;Holman et al, 2018;Stroebel et al, 2018;Amat et al, 2019;McMullen et al, 2020;Zeineldin et al, 2020a). Analogously, predicting when and how respiratory microbiome breaks down is at the heart of several studies in swine (Cortes et al, 2018;Zeineldin et al, 2018;Jakobsen et al, 2019;Megahed et al, 2019;Mou et al, 2019;Wang et al, 2019;Pirolo et al, 2021). For instance, it appears as though that during weaning, several microorganisms act synergistically to mediate the BRDC (Gaeta et al, 2017;Klima et al, 2019;McMullen et al, 2019;Zeineldin et al, 2019) and PRDC (Wang et al, 2018;Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation